A Human–AI Interaction Model for Improving Speaking Skills in EFL Learning using ChatGPT - Zulianingrum, Ana; Manggolo, Noor Sahid Kusuma Hadi (Nusantara Journal of Artificial Intelligence and Information Systems, 2025)
This study investigates the role of ChatGPT in enhancing English as a Foreign Language (EFL) students' speaking skills. The primary aim is to explore whether integrating ChatGPT into language learning can effectively improve speaking proficiency. Using a controlled experimental design, participants were divided into treatment and control groups, with the treatment group utilizing ChatGPT for speaking practice. The results demonstrated significant improvements in speaking skills for the treatment group, with statistical analysis confirming the rejection of the null hypothesis. This study highlights the technical capabilities of ChatGPT in offering personalized, adaptive learning experiences, showcasing its potential in language education. The findings emphasize the importance of AI tools like ChatGPT in enhancing language learning outcomes. Furthermore, it calls for educator training to harness AI effectively in pedagogical strategies. Overall, the study affirms that ChatGPT is a powerful, accessible tool for improving speaking skills, offering scalable solutions in EFL education.